Murder on the border - Traversari, Gabriel; Acosta, Alpha; Lo, Siboney; Roberts, North; Huicochea, Roberto; Frausto, Juan J.; Maverick Entertainment, Inc. (Deerfield Beach, FL : Maverick Entertainment Group, 2005)
A Hispanic attorney's life is turned upside down when his family decides to cross the border illegally. At the same time, a police officer is charged with the shooting death of a young Latino boy at the U.S.-Mexican border. The attorney is assigned to defend him.
Special features: Interactive menu, trailers, scene selections.
Directed by Juan J. Frausto.
Gabriel Traversari, Alpha Acosta, Siboney Lo, North Roberts, Roberto Huicochea.
Preschool
DVD
In English with Spanish subtitles.
Keywords: Illegal aliens -- Crimes against -- Mexican-American Border Region -- Drama; Illegal aliens -- United States -- Drama; Video recordings for the hearing impaired; United States -- Emigration and immigration -- Drama; Mexico -- Emigration and immigration -- Drama